Implementasi Aplikasi Mobile untuk Meningkatkan Keselamatan Turis di Tujuan Wisata Berisiko Tinggi - Sulistiyanta, Nur Linda; Ignatius Wahyu Widodo; -, Suyoto (Fakultas Teknik Universitas Hamzanwadi, 2025)
The competitiveness of smart tourism destinations depends on the natural and cultural attractions, infrastructure, and quality of services offered, including security and safety as the main factors in choosing a tourist destination by tourists. The purpose of this study is to determine mobile applications to improve tourist safety in high-risk tourist destinations. This research is a systematic review (Systematic Literature Review). Data is processed and presented in the form of a description. The study results show that a mobile application can be an alternative to improve tourist safety, especially in high-risk tourist destinations. A mobile application can be developed to improve tourist safety, especially in high-risk tourist destinations so that they feel satisfactory service. Satisfactory service can certainly provide a positive experience for tourists. The application can also be developed with the application of artificial intelligence and various features to improve user experience. These services can be in the form of safe transportation route features for tourist destinations such as medical tourism. Mobile applications with real-time features can also make it easier for tourism managers to monitor tourists so that they continue to carry out activities safely. Therefore, the application can also be made specifically to overcome disasters and can be a tool to provide information to tourists, increase their awareness of risks, and improve their preparedness for disasters